2020
DOI: 10.1016/j.ijgfs.2019.100193
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing the preparation of the Malaysian mixed rice dish (MRD) with Cook-Chill Central Kitchen and implementation of HACCP

Abstract: This paper demonstrated the implementation of a Cook-Chill central kitchen to automate the preparation of traditional mixed rice dish (MRD) and its food hazard analysis based on Hazard Analysis and Critical Control Point (HACCP) program. The preparation of the MRD is commonly associated with the traditional home-style kitchen, tedious manual processes and uncontrolled food hazards that caused serious illness including fatalities. In this paper, the conventional preparation of the dishes was transformed into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…However, after being stored for 15 days at 20±2 ℃, the yeast count significantly increased to 3.8 ×10 4 CFU/g, while the mold count reached 9.0 ×10 3 CFU/g. These counts exceeded the maximum allowable limit of 1.0 ×10 2 CFU/g for yeast and mold in ready-to-eat foods, as stated in the Food and Drug Administration Food Code (Hasnan & Ramli, 2020). The growth of yeast and mold in the GC samples was feasible since their acid/alkaline requirement for growth was quite broad, ranging from pH 2 to above pH 9.…”
Section: Effect Of Ambient Storage On Microbiological Countsmentioning
confidence: 86%
“…However, after being stored for 15 days at 20±2 ℃, the yeast count significantly increased to 3.8 ×10 4 CFU/g, while the mold count reached 9.0 ×10 3 CFU/g. These counts exceeded the maximum allowable limit of 1.0 ×10 2 CFU/g for yeast and mold in ready-to-eat foods, as stated in the Food and Drug Administration Food Code (Hasnan & Ramli, 2020). The growth of yeast and mold in the GC samples was feasible since their acid/alkaline requirement for growth was quite broad, ranging from pH 2 to above pH 9.…”
Section: Effect Of Ambient Storage On Microbiological Countsmentioning
confidence: 86%
“…Metaxopoulos et al [10] also showed that the HACCP system and GHP were applied in Greece via the meat industry and proved the importance of safety assurance programs' application together with high-quality raw materials, product handling and staff training. Additionally, Hasnan and Ramli [44] demonstrated that the HACCP system allows suitable handling activities, hygienic conditions and effective safety procedures, which presents valuable knowledge for entrepreneurs. Furthermore, Wang et al [45] showed that the effective HACCP system and plan can eliminate chemical and microbiological contaminants in vacuum-packed sauced pork.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella spp. та E. coli є мезофільними організмами, які найкраще ростуть за помірних температур в діапазоні 5-46 °C [12].…”
Section: рис 2 -діаграма аналізу ризику рис 3 -критерії оцінювання вп...unclassified